Ammonia volatilization and agronomical efficiency of a mixture of urea with natural zeolite for rose fertilization - Werneck, Carlos Guarino; Haim, Patrick Gesualdi; Breda, Farley Alexandre da Fonseca; Monte, Marisa Bezerra de Mello; Bernardi, Alberto Carlos de Campos; Mazur, Nelson; Polidoro, José Carlos (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the losses of N-NH3 by volatilization and the agronomic efficiency of a mixture of urea with natural zeolite, as topdressing fertilization, in an area for the commercial production of roses (Rosa spp.). The treatments were: two rates of urea (60 and 120 kg ha-1), with and without zeolite. The N sources were applied directly to soil surface, and volatilization was determined using a free semi-open static chamber. The quantitative and qualitative variables of the collected flower stems were used to determine the agronomical efficiency of the fertilizers. The zeolite mixture reduces N-NH3 losses in 30%, compared with the commercial urea fertilizer, and shows a higher agronomic efficiency, resulting in an increase of 25 dozen of flower stems per each kilogram of N applied.